Finding me eaudiobook A decade of darkness, a life reclaimed: a memoir of the cleveland kidnappings. - Knight, Michelle (Recorded Books Inc., 2014)
Michelle was a young single mother when she was kidnapped by a local school bus driver named Ariel Castro. For more than a decade afterward, she endured unimaginable torture at the hand of her abductor. In 2003 Amanda Berry joined her in captivity, followed by Gina DeJesus in 2004. Their escape on May 6, 2013, made headlines around the world. Barely out of her own tumultuous childhood, Michelle was estranged from her family and fighting for custody of her young son when she disappeared. Local police believed she had run away, so they removed her from the missing persons lists fifteen months after she vanished. Castro tormented her with these facts, reminding her that no one was looking for her, that the outside world had forgotten her. But Michelle would not be broken. In Finding Me, Michelle will reveal the heartbreaking details of her story, including the thoughts and prayers that helped her find courage to endure her unimaginable circumstances and now build a life worth living. By sharing both her past and her efforts to create a future, Michelle becomes a voice for the voiceless and a powerful symbol of hope for the thousands of children and young adults who go missing every year.